Socioeconomic conditions exacerbated by the coronavirus in the Eastern Cape province of South Africa - Raphela, Tlou D.; Tjantjies, Sinoyolo (Frontiers in Public Health, 2025)
IntroductionSouth Africa, like most developing countries, made some efforts to attain the Sustainable Development Goals by endeavoring to reduce individuals' susceptibility to socio-economic hardships. However, the COVID-19 pandemic eroded most of those efforts. In this seemingly helpless situation, it is apparent that the coronavirus has compromised the commendable strides made toward achieving some of the efforts toward attaining some of these Sustainable Development Goals. This article, therefore, analyses the socioeconomic conditions exacerbated by COVID-19 on the East Coast of South Africa.MethodologyThe study adopted a quantitative research-method approach to quantify this socio-economic disparities and applied, descriptive statistics, chi-squared test of independence, and regression to analyse the data collected using a semi-structured questionnaire survey at a rural community in the Eastern Cape of South Africa. Simple random sampling was adopted for this study and Statistical Package for Social Scientists was used to analyse the data collected.ResultsThere was no significant relationship when the question of whether the municipality has adequately implemented measures to ensure the socio-economic protection of communities was regressed with other 3 Likert scale questions (χ2 = 95.98; df = 77; P = 0.07; R2 = 38.0%). A series of Chi-square tests did not reveal any statistically significant difference in five demographic variables and the variables they were correlated with (P > 0.05). However, there was a statistically significant difference between most questions relating to the effectiveness of the COVID-19 response strategies the municipality employed and participants' response to unmet community social needs (X2 = 35.754; df = 14; P = 0.001).Discussions and conclusionsThis study, therefore, revealed that social significance does not necessarily mean statistically significant following the results of the insignificant chi-squared test for the socio-economic and demographic variables. This study also sheds light on the profound impact of the COVID-19 pandemic on the socioeconomic landscape of the East Coast of South Africa. Despite commendable strides toward achieving Sustainable Development Goals aimed at reducing vulnerabilities to socio-economic hardships, the pandemic has presented daunting challenges, disrupting progress and exacerbating existing inequalities coupled with efforts of the study Municipalities strategies.